Strategi Promosi Dalam Meningkatkan Penjualan Produk Usaha Keripik Talas Desa Padende Kecamatan Marawola Kabupaten Sigi - Muladi Muladi; Ahmad Syatir; Wiri Wirastuti (Pusat Riset dan Inovasi Nasional, 2023)
The MBKM ( Independence Learing Independent Campus ) activity organized by the Faculty of Economics and Business, Tadulako University which was held on September 6 2022 to January 10 2023, located in Padende Villsge, Marawola District, Sigi District, we received very good enthusiasm from the local community. The promotion strategy in increasing sales of taro chips business products in Padende Village Marawola sub-district, Sigi district must carry out promotions so that these products can be sold, there are several factors that make taro chips products not develop, namaly: There is no cooperation with the business actors, do not carry out public promotions, or promotions on social media. The aim of this research is to help taro chips products increase sales and be able to compete with other chipproducts.The social approach here is an attempt by universities, especially MBKM students as the main actors in MBKM to integrate themselves (assimilate themselves) into various community activites at the MBKM location. Shep in the process of taro chips products: Observing and surveying taro chips products, and analyzing the taro chip product itself.